Survival of a patient with multiple-recurrent giant retroperitoneal dedifferentiated liposarcoma for 15 years: A case report - Xia, Hao; Fang, Fang; Yuan, Haijuan; Tu, Yimei (Frontiers in Surgery, 2022)
Background: Retroperitoneal liposarcoma(RPLS) is a variety of soft tissue sarcomas originates from mesenchymal cells. The tumor measuring greater than 30 cm is called “giant liposarcoma”. Part of the neoplasms tend to multiple recur locally or metastasize distantly. For the higher mortality, the long-term survival is uncommon. Therefore, it’s necessary to present an uniform and optimized program to improve the prognosis. Methods By succeeded in treating a multiple-recurrent giant retroperitoneal dedifferentiated liposarcoma(RP DDLPS) in July 2010, we may expect inducing more comprehensive strategies to improve diagnosis, therapy and outcome. Results In July 2010, we thoroughly resected a giant multifocal RPLS with concomitant part of the gastric wall. The histopathological examination revealed a high-grade(grade Ⅲ), dedifferentiated liposarcoma. The patient was discharged uneventfully on the 15th postoperative day. She relapsed sixteen months later, and underwent another complete excision. After nine months, she died for the fourth recidive. The patient had respectively experienced four times recurrences and operations with fifteen years of follow-up. Conclusions It demonstrates that we successfully treated the multi-recurrent giant RPLS in poor medical conditions by meticulous management, meanwhile, it indicates long-term survival could be achieved for high grade RP DDLPS.